DEVELOPMENT OF MONOPOLY BOARD GAMIFICATION MEDIA BASED ON PROJECT-BASED LEARNING TO IMPROVE MATHEMATICAL CONCEPT UNDERSTANDING - Angel Ardila Suci Q A; Ni Nyoman Parwati; I Gde Wawan Sudatha (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study aims to develop a gamification board monopoly media based on Project Based Learning (PjBL) to improve mathematical concept understanding of elementary school students on solid geometry material. This research and development used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study was conducted at SDN Jatian 01 Jember with 25 fifth-grade students as subjects. The research instruments included material and media validation questionnaires using the Learning Object Review Instrument (LORI), a User Experience Questionnaire (UEQ) for teachers and students, and concept understanding tests (pretest–posttest). Results showed that the Polymath Space board monopoly media achieved a material validity score of 4.7 (95%, very valid) and media validity of 4.7 (93%, very valid). The UEQ practicality assessment from three teachers showed excellent ratings in attractiveness (2.06), efficiency (1.92), stimulation (2.00), and novelty (2.00). Students also rated the media positively, with excellent scores in clarity (2.07), appropriateness (2.02), stimulation (1.86), and novelty (2.04). The mean pretest score was 62.30 and posttest was 82.20. The Shapiro-Wilk normality test showed both data sets were normally distributed (sig. 0.620 and 0.697 > 0.05). The Levene homogeneity test indicated homogeneous variances (sig. 0.082 > 0.05). The paired sample t-test showed a significant improvement (sig. 0.000 < 0.05). The Cohen’s d effect size was 1.65 (large effect). Learning mastery based on KKM (score ≥ 75) reached 92%, categorized as very effective. This media is valid, practical, and effective in improving mathematical concept understanding. Learning (PjBL) untuk meningkatkan pemahaman konsep matematika siswa sekolah dasar pada materi bangun ruang sisi datar. Penelitian pengembangan ini menggunakan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Penelitian dilaksanakan di SDN Jatian 01 Jember dengan subjek 25 siswa kelas V. Instrumen penelitian meliputi angket validasi materi dan media menggunakan Learning Object Review Instrument (LORI), User Experience Questionnaire (UEQ) untuk guru dan siswa, serta tes pemahaman konsep (pretest–posttest). Hasil penelitian menunjukkan media board monopoly Polymath Space memperoleh skor validitas materi 4,7 (95%, sangat valid) dan validitas media 4,7 (93%, sangat valid). Penilaian kepraktisan UEQ dari tiga guru menunjukkan kategori excellent pada daya tarik (2,06), efisiensi (1,92), stimulasi (2,00), dan kebaruan (2,00). Siswa juga menilai positif dengan kategori excellent pada kejelasan (2,07), ketepatan (2,02), stimulasi (1,86), dan kebaruan (2,04). Rata-rata pretest sebesar 62,30 dan posttest sebesar 82,20. Uji normalitas Shapiro-Wilk menunjukkan kedua data berdistribusi normal (sig. 0,620 dan 0,697 > 0,05). Uji homogenitas Levene menunjukkan varians homogen (sig. 0,082 > 0,05). Uji paired sample t-test menunjukkan peningkatan signifikan (sig. 0,000 < 0,05). Nilai effect size Cohen’s d sebesar 1,65 (efek besar). Ketuntasan belajar berdasarkan KKM (≥75) mencapai 92% dengan kategori sangat efektif. Media ini terbukti valid, praktis, dan efektif dalam meningkatkan pemahaman konsep matematika.